1986
DOI: 10.1097/00000658-198612000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidation of Body Fuel Stores in Cancer Patients

Abstract: In an attempt to define the mechanism of weight loss in cancer patients, fat and carbohydrate oxidation rates were calculated in 93 patients. Seventy patients with colorectal or gastric cancer were compared with a control group of 23 patients with nonmalignant illness. Twenty-seven patients with cancer and 13 control patients had lost more than 10% of their pre-illness body weight. Fat and carbohydrate oxidation rates were derived from measurements of oxygen consumption, carbon dioxide production, and urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 19 publications
2
17
0
1
Order By: Relevance
“…This disturbance has been described predominantly for the postabsorptive state [26,27] and for euglycemic clamp situations [4,5], but has also been observed during parenteral nutrition [27]. Whole-body glucose oxidation is reduced in the fasting state [6,7] and also tends to be lowered after meals [28]. An inability to deposit normal amounts of glucose as glycogen [3][4][5], not only in the liver [29] but also in muscle [4], appears to be one of the most profound disorders of glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This disturbance has been described predominantly for the postabsorptive state [26,27] and for euglycemic clamp situations [4,5], but has also been observed during parenteral nutrition [27]. Whole-body glucose oxidation is reduced in the fasting state [6,7] and also tends to be lowered after meals [28]. An inability to deposit normal amounts of glucose as glycogen [3][4][5], not only in the liver [29] but also in muscle [4], appears to be one of the most profound disorders of glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…During parenteral nutrition, peripheral fatty acid uptake was found to be in the reference range [27]. Lipid oxidation is intensified in postabsorptive cancer patients [3,6,7], and the clearance of lipid emulsions is accelerated [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 BMI < 18 and low serum albumin predict 30-day mortality in esophageal cancer. 15 For older adults the recommended daily water intake is 30 ml/kg, 16 calorie intake 23 and 25 kcal/kg in stable weight and weight losing patients respectively 17 and protein intake of 1.2 to 2 g. 18 Based on a Cochrane review, four randomized trials on cancer patients revealed a decrease in mortality when intake of oral supplements was ≥400 kcal/day in patients ≥75-yrs old and supported for >35-days. 19 …”
Section: Nutrition and Cancer Treatment Outcomementioning
confidence: 99%
“…48 reported elevated TG and VLDL in 25 patients with acute leukemia and lymphoma. Hansell et al 49 reported an increased rate of fat oxidation in 70 patients with either colorectal or gastric cancer especially those with weight loss or liver metastasis.…”
Section: Protein Metabolismmentioning
confidence: 99%